Analysis Financial Distress at PT Blue Bird Tbk Period 2016-2021 - Nur Qaidah Agsa; M. Ikhwan Maulana Haeruddin; Anwar Anwar (Cita Konsultindo Research Center, 2022)
This study aims to analyze financial distress at PT Blue Bird Tbk using the measurement model Springate and Zmijewski. This study uses a descriptive quantitative approach. The population in this study is the financial statements of PT. Bluebird Tbk. Then the sample in this study is the financial statements of PT. Blue Bird Tbk in 2016-2021. Data were analyzed using the measurement model Springate and Zmijewski. The results of the study illustrate that by using the model Springate PT Blue Bird Tbk in 2016-2018 is in good health. But in 2019-2021 PT Blue Bird Tbk experienced conditions financial distress. While the model Zmijewski shows that PT Blue Bird Tbk in 2016-2021 experienced a condition Non-Financial distress or in good health. Keywords: Financial distress, Springate, Zmijewski